1970
DOI: 10.3126/jnps.v31i3.5357
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Findings during Canal Wall Down Mastoidectomy in Children

Abstract: Objective: The main objective of this study is to assess the intraoperative finding during canal wall down mastoidectomy in paediatric patients undergoing surgery for unsafe type of chronic suppurative otitis media (CSOM) attending ENT OPD of Kathmandu Medical College. Materials and Methods: Fifty patients of age group 4 to 13 years who were suffering from unsafe type of CSOM with or without cholesteatoma were taken for the study. The study period was two years from April 2007 to March 2009. The operative find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Kartush found erosion of long process of incus with an intact malleus handle and stapes superstructure (type A) as the most common ossicular defect [17]. Shreshtha et al and Mathur et al also reported similar findings in unsafe CSOM [18,19].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Kartush found erosion of long process of incus with an intact malleus handle and stapes superstructure (type A) as the most common ossicular defect [17]. Shreshtha et al and Mathur et al also reported similar findings in unsafe CSOM [18,19].…”
Section: Discussionmentioning
confidence: 85%
“…Sade et al reported stapes involvement in unsafe CSOM to be 36.00% [5]. Shreshtha et al found involvement of stapes superstructure in 15.00% cases of unsafe CSOM [18]. Motwani et al reported stapes arch necrosis in 30.00% cases of CSOM [20].…”
Section: Discussionmentioning
confidence: 99%
“…Our study 75 Austin [9] 15.5 Sade et al [10] 36 Shrestha et al [11] 15 Motwani et al [12] 30 Varshney et al [5] 51.67…”
Section: Author Of the Study Percentage Of Stapes Erosionmentioning
confidence: 91%
“…In the present study, the most common pathology was found to be mixed (52 %), followed by granulation tissue (36 %) and cholesteatoma (12 %). 9 One of the observational study demonstrated that cholesteatoma with granulation was present in 72 %, granulation tissue in 16 % and cholesteatoma in 12 % 9 . Involvement of tympanic and mastoid cavities was seen in majority of cases.…”
Section: Discussionmentioning
confidence: 99%